Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds. Implementing TIME at home: Insights from caregivers - von Blottnitz, Magali (Wordworks, 2024)
This is the fourth in a series of learning briefs that explore the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds. This brief is based on interviews, home visits and observations made between February 2022 and August 2023 with participating families of children who were in Grade R in 2022 and in Grade 1 in 2023. It focuses on the home circumstances of families and their lived experiences while engaging with the TIME programme. This brief seeks to address the following questions: • How does the diversity of families and homes challenge our mental representations of “family” and “home”? • What does it take to embed the practice of TIME in the routine of the home? • What can we learn from caregivers’ experiences with TIME at home, which could help improve the frequency and the quality of families’ engagement? Reviewing the stories of a few families under a dynamic lens, the brief discusses how home circumstances such as family configurations, poverty, working hours, multilingualism, influence the levels of caregiver engagement with the TIME programme, and draws a typology of caregiver engagement.
TIME Learning Brief 4
More information about the TIME (Together in My Education) home-learning programme and materials can be found in open access at: https://wwhomeliteracy.org.za/time/
Keywords: Early learning; Early literacy; South Africa; Wordworks; Home-learning; Parental involvement; Longitudinal study; Grade R; Grade 1; caregiver engagement; Multilingualism